2020
DOI: 10.1148/radiol.2020201754
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Chest Radiography Features Determine Patient Outcomes in Young and Middle-aged Adults with COVID-19

Abstract: Background: Chest radiography (CXR) has not been validated for its prognostic utility in evaluating patients with coronavirus disease 2019 .Purpose: The purpose of this study was to analyze the prognostic value of a CXR severity scoring system for younger (non-elderly) patients with COVID-19 upon initial presentation to the emergency department (ED). Outcomes of interest included hospitalization, intubation, prolonged stay, sepsis, and death. Materials & Methods:In this retrospective study, patients between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

55
415
7
22

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(499 citation statements)
references
References 21 publications
55
415
7
22
Order By: Relevance
“…Also, in our study there was a signi cant association between symptoms and chest x-ray ndings. This nding should encourage the health professionals to utilize chest x-ray in the diagnosis and follow up of patients with COVID-19 which is in agreement with a study conducted by Toussie et al who reported that chest xray severity score was found to be a predictive index of risk for hospital admission and intubation (29), and mobile chest x-rays were found to be bene cial in the follow up of critically ill COVID-19 patients in another study (27).…”
Section: Discussionsupporting
confidence: 88%
“…Also, in our study there was a signi cant association between symptoms and chest x-ray ndings. This nding should encourage the health professionals to utilize chest x-ray in the diagnosis and follow up of patients with COVID-19 which is in agreement with a study conducted by Toussie et al who reported that chest xray severity score was found to be a predictive index of risk for hospital admission and intubation (29), and mobile chest x-rays were found to be bene cial in the follow up of critically ill COVID-19 patients in another study (27).…”
Section: Discussionsupporting
confidence: 88%
“…Further, the risk of MERS-CoV mortality in our group was found to be highest when patients where >44 years-old. Herein lies another similarity with recent observations of COVID-19, of which older age and more substantial lung involvement are associated with poorer prognosis 8,17,30 .…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, the reported imaging magni cations of both viruses are remarkably similar [7][8][9] . The utility of chest X-rays (CXRs) in investigating MERS-CoV and COVID-19 is practically convenient, yet the number of dedicated studies addressing the CXR ndings of both coronaviruses is limited, especially when compared to that of their CT features 6,[10][11][12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Chest radiography imaging, which can be either x-rays or CT (Computed Tomography) scans has important applications in the diagnosis of COVID-19 [17]. Medical professionals use these scans of the chest of the patient to get more information about the presence and extent of the virus, the severity of the spread as well as regions of infection.…”
Section: Introductionmentioning
confidence: 99%